التمويل بالمضاربة في نافذة النور الإسلامية في بنك سيلاني التقليدي وقضية مدى كفايتها لحاجة الأقلية المسلمة السريلانكية: دراسة مقاصدية : Mudarabah Financing in the An-Noor Islamic window of Bank of Ceylon and the Issue of Its Adequacy to the needs of the Sri Lankan Muslim minority: A Maqasid Study - Mohamed Akbar Kareem , Mohamed Bishrul Rifath; Ghalia, Bouhedda; Mohammed Jiffry , Arafath Careem (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
تهدف هذه الورقة البحثية إلى التعرض لمنتج المضاربة الذي تقوم به ‏نافذة النور الإسلامية في بنك سيلاني التقليدي بسريلانكا تم تأسيسها عام (٢٠٠٩م)، وذلك أنها تحاول تقديم الحلول لإشكالية تمويل المضاربة المعمول بها والمتناسقة لواقع الأقلية المسلمة السريلانكية من خلال توظيف مقاصد الشريعة، والحقيقة أن ظهور النوافذ الإسلامية في المصارف التقليدية المؤسسة على الربا المحرم أصبحت قضية مستجدة بالنسبة لإطار العمل المصرفي الإسلامي المعاصر. لكن هناك إشكاليات عديدة تعاني منها نافذة "النور" الإسلامية في بنك سيلاني التقليدي بسريلانكا باعتبارها كنافذة في الهيكل المصرفي التقليدي الربوي، ويلاحظ أن المستجدات الفقهية بأمس حاجة إلى الحل الفقهي المناسب مع ظروف الأقلية المسلمة السريلانكية؛ ومن تلك القضايا الرأسمال لفتح النافذة ومدى استقلاليتها في نشاطاتها ومنتجاتها المصرفية كالمضاربة والتي تتطلب التكييف الفقهي من منظور فقه الأقليات وبعد مقاصدي وأيضا تتطلب التفعيل بالتوسع فيها بما يكفي حاجات الأقلية في التمويل. ولأجل تحقيق ذلك؛اعتمدت هذه الورقة البحثية على المنهج الاستقرائي في تتبع محتويات الموضوع وجمع المادة العلمية، زيادة على المنهج التحليلي والمقارن في الشرح والاستنتاجات والمناقشات. وتمكنت الدراسة من التوصل إلى أهم النتائج، وهي كما يلي؛ إن منتج المضاربة المصرفية في نافذة النور لا تزال بحاجة إلى مزيد من التطوير، بحيث أن آلياتها مستقلة، وأن تتم عملية التدقيق في ضوء ما تعرفه تجارب النوافذ في دول أخرى. كما أن نشر الوعي بأن المصرفية الإسلامية أحد أهم الوسائل المعينة على النهوض بالاقتصاد الوطني بشكل عام، وأنها تعمل على ضمان حفظ المال وتنميته كأحد الضروريات الخمس؛ وبذلك تتغير النظرة الضيقة لدى الأغلبية من غير المسلمين الأغلبية نحو المصرف الإسلامي. This research paper aims to expose the Mudaraba product that is carried out by the An-Noor Islamic window of the conventional Bank of Ceylon in Sri Lanka, which was established in (2009 AD). The phenomenon of the Islamic window of conventional banks based on forbidden usury has become a new challenge for the contemporary Islamic banking framework. However, there are many problems that the Islamic window suffers from in general. They are related to the An-Noor Islamic window as a window in the traditional usurious banking structure. These issues need to be addressed and exposed to jurisprudential calamities which are in dire need of a juristic solution consistent with the context of the Sri Lankan Muslim minority. This is because the capital gained to open the window in the conventional bank and the extent of its independence in passing its banking activities and products such as Mudaraba requires jurisprudential intervention from the perspective of higher objectives of Shariah. Through employing the qualitative method and thematic analysis, this study found that the Mudarabah product in the An-Noor Islamic window still needs further development so that its mechanisms are independent. In addition, the Mudarabah finance product can accommodate and adapt the most suitable aspects from the experiences of windows in other countries. Furthermore, the audit process deployed in other countries can also be adapted to suit the Islamic Window context. Creating awareness that Islamic banking is one of the most important means for the advancement of the national economy in general and works to ensure the preservation and development of money as one of the five necessities of Islamic Shariah. Thus, the attitude of other communities toward the Islamic banking system could change positively.